Risk and return in the bond markets: Past developments and future prospects - Allan Bødskov Andersen; Jakob Lage Hansen (Danmarks Nationalbank, 2006)
The paper examines the past risk and return trade-off on the US bond market, and uses this as a basis for developing a flexible tool based on simulation of principal components to evaluate future prospects for risk and returns for investors. The principal components of the yield curve are related to a few main macro-economic drivers (inflation and real GDP-gap). This allows simulation of yields curves based on expectations about the future behaviour of the macro-economic drivers, rather than relying solely on parameters estimated from historic data. The overall conclusion is that since 1960 the US-bond market has rewarded risk in the sense that more volatile bond returns has been associated with higher average realized returns. However, this covers very large variation over sub-periods, and in periods with increasing yield trend extra risk has not always been rewarded. In the simulations of the future risk-return trade-off, there are lower excess returns from enhancing the duration exposure in the future relative to the near past. However, the risk associated with duration enhancing is also lower.
Keywords: 330